Numerical Simulation of Rock Dynamic NSCB Test Based on a Self-Developed Dynamic Damage Model - Hu, Xuelong; Duan, Minke; Tu, Min; Zhang, Xiangyang; Zhang, Ming; Xu, Wenyao (Frontiers in Earth Science, 2022)
Elucidating and understanding the dynamic fracture characteristics of rocks play an essential role in the application of rock engineering and geophysics. In this paper, based on a self-developed dynamic damage model, rock notched semi-circle bend test with SHPB technique is numerically simulated. The paper focuses on three aspects including damage evolution, energy evolution and failure mode of rock under different loading velocities. From the simulated results, the following conclusions can be conducted: 1) the damage range increases gradually with the increase of loading velocity; 2) the crack propagates to the loading point along the symmetry axis of the samples under different loading velocities; 3) the loading velocity has an important influence on the failure mode of straight notch semi-circular marble, whose mechanism can be explained by that the local high strain rate leads to the obvious randomness and uncertainty of crack activation in rock; 4) the energy evolution of NSCB is vitally affected by loading velocity, and the deformation and failure process of straight notch semicircular marble under dynamic loading can be divided into five stages according to the ratio of internal energy to total energy. The beneficial findings maybe provide some references in practice design from engineering problems.